An Intuitionistic Fuzzy Graph’s Signless Laplacian Energy - Ramesh, Obbu; Sharief Basha, S. (International Journal of Engineering and Technology, 2018)
We are extending concept into the Intuitionistic fuzzy graphâ€™ Signless Laplacian energyÂ instead of the Signless Laplacian energy of fuzzy graph. Now we demarcated an Intuitionistic fuzzy graphâ€™s Signless adjacency matrix and alsoÂ an Intuitionistic fuzzy graphâ€™s Signless Laplacian energy. Here we find the Signless Laplacian energy â€˜s Intuitionistic fuzzy graphs above and belowÂ Â boundaries ofÂ Â an with suitable examples.Â Â Â